1997
DOI: 10.1515/tjj.1997.14.3.145
|View full text |Cite
|
Sign up to set email alerts
|

Vortex Shedding Behind a Blunt Trailing Edge Turbine Blade

Abstract: By computational and experimental means, this work investigates unsteady mixing processes of the wake behind a blunt trailing edge turbine blade. Numerical solutions of the Reynolds averaged Navier Stokes equations have been earned out employing state-of-the-art algorithms in a fully conservative structured multi-block approach.Predicted aerodynamic performance profile and unsteady flow field features compare favorably with a set of measurements carried out on a large scale nozzle guide vane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 6 publications
4
14
0
Order By: Relevance
“…The numerical nonuniform pressure distribution along the trailing edge surface confirms the experimental data 17) and is different from the uniform pressure distribution observed experimentally by Cicatelli and Sieverding 14) and confirmed numerically by Sondak and Dorney 15) and Cicalelli et al 16) at low Mach number. El-Gendi et al 21) showed that this non-uniform pressure distribution results from highly unsteady pressure fluctuations caused by vortex formation close to the trailing edge at this high Mach number, M 2is ¼ 0:79.…”
Section: Distributions Of Time-average Pressure In Trailingsupporting
confidence: 74%
See 2 more Smart Citations
“…The numerical nonuniform pressure distribution along the trailing edge surface confirms the experimental data 17) and is different from the uniform pressure distribution observed experimentally by Cicatelli and Sieverding 14) and confirmed numerically by Sondak and Dorney 15) and Cicalelli et al 16) at low Mach number. El-Gendi et al 21) showed that this non-uniform pressure distribution results from highly unsteady pressure fluctuations caused by vortex formation close to the trailing edge at this high Mach number, M 2is ¼ 0:79.…”
Section: Distributions Of Time-average Pressure In Trailingsupporting
confidence: 74%
“…Regarding this issue, Desse 13) conducted an experiment for flat plates, and Cicatelli and Sieverding 14) considered a turbine cascade with M 2,is ¼ 0:4. Sondak and Dorney 15) and Cicalelli et al 16) investigated this problem numerically using the same cascade and flow conditions as Cicatelli and Sieverding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ó 2013 The Japan Society for Aeronautical and Space Sciences Cicatelli and Sieverding 6) found a uniform pressure distribution at the TE of a turbine cascade at M 2;is ¼ 0:4. Sondak and Dorney 7) and Manna et al 8) numerically confirmed this distribution using the same cascade and flow conditions as Cicatelli and Sieverding. 6) Sieverding et al 9) conducted experiments at M 2;is ¼ 0:79 on a cascade with half the scale of that used in other research.…”
Section: Introductionmentioning
confidence: 55%
“…6) Sieverding et al 9) conducted experiments at M 2;is ¼ 0:79 on a cascade with half the scale of that used in other research. [6][7][8] They noticed that the TE pressure distribution is non-uniform. This non-uniformity decreases the average value of the base pressure and hence increases the TE loss.…”
Section: Introductionmentioning
confidence: 99%